2016
DOI: 10.1002/cjas.1399
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of demographic characteristics on the relationship between strategic capabilities and firm performance in women‐owned entrepreneurial ventures in Nairobi, Kenya

Abstract: This study is motivated by the need to understand the determinants of performance in women-owned enterprises. We examine the relationship between strategic capabilities and firm performance with demographic characteristics as moderators in women-owned enterprises in Nairobi, Kenya. Results show that strategic capabilities have a significant effect on the overall performance. Further, IT capabilities and technological capabilities have a positive and significant relationship with performance. Only age has a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 76 publications
(127 reference statements)
1
55
0
1
Order By: Relevance
“…Previous research has shown that the lack of management skills and functional business skills can be an obstacle in running a business (Leibestein, 1968;Lerner & Haber, 2001). Management skills have also been found by numerous researchers to be positively related to firm performance (Mari et al, 2016;Prasad et al, 2013;Rey-Marti, Porcar, & Mas-Tur, 2015;Staniewski, Janowski, & Awruk, 2016), although, as in the previous case, some studies point to a lack of such a relationship (Kimosop et al, 2016). By achieving an adequate level of management skills to manage her business, the woman entrepreneur will most likely increase the chances for her business to be successful (Lerner et al, 1997;Buttner, 2001;Huarng et al, 2012;Mitchelmore & Rowley, 2013).…”
Section: Control Variablesmentioning
confidence: 89%
See 4 more Smart Citations
“…Previous research has shown that the lack of management skills and functional business skills can be an obstacle in running a business (Leibestein, 1968;Lerner & Haber, 2001). Management skills have also been found by numerous researchers to be positively related to firm performance (Mari et al, 2016;Prasad et al, 2013;Rey-Marti, Porcar, & Mas-Tur, 2015;Staniewski, Janowski, & Awruk, 2016), although, as in the previous case, some studies point to a lack of such a relationship (Kimosop et al, 2016). By achieving an adequate level of management skills to manage her business, the woman entrepreneur will most likely increase the chances for her business to be successful (Lerner et al, 1997;Buttner, 2001;Huarng et al, 2012;Mitchelmore & Rowley, 2013).…”
Section: Control Variablesmentioning
confidence: 89%
“…Shi and Dana (2013) found that the socialization patterns of second-generation, small to medium Chinese family businesses' owner-managers have a significant effect on the entrepreneurship processes in the business, which reflects the relationship between market orientation and entrepreneurship. Kimosop et al (2016) found that marketing capabilities have a significant and positive effect on the performance of firms managed by women entrepreneurs in the emerging economy of Kenya. They suggest that, for women to improve their firms' performance, they must build on marketing capabilities.…”
Section: Marketing Capabilities and Firm Performancementioning
confidence: 99%
See 3 more Smart Citations